The Impact of Corporate Sustainability Practiceson Consumers’ Brand Loyalty - KARAYEL BİLBİL, EMEL (My University, 2023)
In the intensely competitive environment that is increasing day by day around the world, organizations do not have many options to survive, and creating a difference is one of the most effective ways a company can resort to in this regard. In such an environment, while some organizations make a difference with their advertisements, some with their products, and others attract attention by considering social benefits. Today, consumers, when purchasing a product, do not only consider its quality and price but also pay attention to how sensitive the company producing that product is to the environment and the world, and the corporate social responsibility activities that the brand is currently involved in. Today, the majority of conscious consumers prefer companies that produce products in compliance with ethical rules and with respect for the environment and nature, and that implement corporate social responsibility practices. To that end, this study at hand aims to determine the extent to which the brand loyalty felt by the target audience towards brands that implement sustainability practices affects consumers' brand purchasing processes. This study will be important in terms of revealing the variables that are effective in the relationship between corporate sustainability practices being implemented in Turkey and consumer brand loyalty. In this context, it is thought that the research will contribute to the literature. Additionally, the data obtained regarding corporate sustainability practices of the organizations related to the research to be conducted in the home appliances sector will also contribute to the literature. For this purpose, firstly, a literature review was conducted on sustainability, corporate sustainability, brand, and brand loyalty, and after the research, the relationship between these concepts was clarified. Subsequently, consumers of Arçelik and Vestel, who are 18 years and older and reside in Istanbul, were reached. A Brand Loyalty (BL) and Corporate Sustainability (CS) scale were developed to measure the brand loyalty created by brands that implement corporate sustainability practices on them, and the survey was conducted on 434 consumers. The data of the research were evaluated using quantitative analysis methods.According to the findings of the research,brand focused on sustainability have been observed to create a positive perception among consumers through their activities aimed at fulfilling their environmental and social responsibilities. The increasing interest and trust of consumers in brands that show sensitivity to the environment and society contribute to the establishment of long-term customer relationship by enhancing the competitive advantage of these brands. Keywords: Sustainability, Corporate Sustainability, Brand, Brand Loyalty, Consumer Behavior
Kurumsal Sürdürülebilirlik Uygulamalarının Tüketicilerin Marka Sadakati Üzerine Etkisi
Keywords: Sustainability; Corporate Sustainability; Brand; Brand Loyalty; Consumer Behavior